Investigation of Interplay of Meaning of Work, Job Pride, and Job Performance on Turnover Intention: Evidence from Millennial Bankers in Central Java, Indonesia - Muttaqin, Masykur Lutfi; Sunaryo, Sinto (Organizations and Markets in Emerging Economies, 2025)
Retaining millennial employees in the workforce is a pressing challenge for organizations. Therefore, this research aimed to investigate the interconnections between the meaning of work, job pride, and job performance, and how job pride and job performance impacted turnover intention of millennials. Cross-sectional surveys of 250 banking employees in Central Java, Indonesia, collected through a multistage sampling procedure were used. In addition, Structural Equation Modeling-Partial Least Square (SEM-PLS) was used to analyze these associations. The results showed significant positive associations among the meaning of work, job pride, and job performance. However, results proposed that job pride and job performance did not negatively affect turnover intention. This research contributed valuable theoretical understanding of the concept of the meaning of work for millennials and offered practical implications for banking managers in human resource management.